Cytogenetic Mapping of 5S and 18S rRNAs and H3 Histone Genes in 4 Ancient Proscopiidae Grasshopper Species: Contribution to Understanding the Evolutionary Dynamics of Multigene Families - Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Martins, C. [UNESP]; Souza, M. J.; Moura, R. C. (Karger, 2010)
This paper reports on the chromosomal location of 18S rRNA, 5S rRNA and H3 histone multigene families in 4 species of a relatively ancient and diversified group of grasshoppers belonging to the family Proscopiidae. The 5S rRNA and H3 histone genes were highly conserved in the number of sites and chromosomal position in the 4th chromosome pair in all species analyzed, whereas the 18S rRNA genes showed slightly more variation because they were present on one or 2 chromosome pairs, depending on the species. The 5S and 18S rRNA gene families occurred in different chromosomes; in contrast, H3 histone and 5S rRNA genes co-localized in the same chromosomal position, with an apparently interspersed organization. Considering that the Proscopiidae family is a relatively ancient group compared with the Acrididae family, the association of the H3 histone and 5S rRNA multigene families can represent a basal condition for grasshoppers, although more research is needed on other representatives of this insect group to confirm this statement. The presence of such an association of 5S rDNA and H3 histone in mussels and arthropods (beetles, grasshoppers and crustaceans) suggests that this linked configuration could represent an ancestral pattern for invertebrates. These results provide new insights into the understanding of the genome organization and the evolution of multigene families in grasshoppers and in insects as a whole. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Chromosomal evolution; FISH; Genome organization; Multigene families; Repetitive DNA